Top-Ten Tips for Dual-Energy CT in MSK Radiology - Walstra, Frances E.; Hickle, Jonathan; Duggan, Peter; Alsharhan, Rashid; Murray, Nicolas; Mallinson, Paul; Munk, Peter; Ouellette, Hugue (Seminars in Musculoskeletal Radiology, 2019)
Dual-energy computed tomography (DECT) has the potential to detect musculoskeletal pathology with greater sensitivity than conventional CT alone at no additional radiation dose to the patient. It therefore has the potential to reduce the need for further diagnostic imaging or procedures (e.g., joint aspirations in the case of gout or magnetic resonance imaging to confirm undisplaced fractures).DECT is a well-established technique for the detection of gout arthropathy. Multiple newer applications have shown clinical potential including bone marrow edema detection and metal artifact reduction. Collagen analysis, bone marrow lesion detection, and iodine mapping in CT arthrography are areas of possible future application and development.This article outlines 10 tips on the use of DECT imaging of the musculoskeletal system, explaining the technique and indications with practical suggestions to help guide the radiologist.
Keywords: dual-energy CT; gout; bone marrow analysis; metal artifact reduction; collagen analysis; iodine mapping